Agricultural value chain finance : tools and lessons - Miller, Calvin; Jones, Linda ([Rome] : Food and Agriculture Organization of the United Nations ; Warwickshire, UK : Practical Action Pub, 2010)
The book provides a comprehensive look at the models, tools and approaches used by industry leaders in all parts of the developing world. These are described, analysed and illustrated by many rich examples in order to demonstrate how they work, and to extract lessons and applications for others to adapt. The book builds on deep experience of the Food and Agriculture Organisation of the UN (FAO) in agricultural development and finance and includes 40 industry examples and 5 comprehensive case studies to enhance learning.
Includes bibliographical references (p. [161]-166) and index.
usc 24/10/17, rpm 05/12/2107
Loans
Keywords: Agriculture; Agriculture--Finance; Agriculture--Economic aspects; Agricultural credit; Agricultural industries; Farm produce--Marketing; Farmers; Developing countries